Complete sequence of a hepatic cirrhosis inbred C57BL/6 mice model mitochondrial genome. (3rd May 2016) - Jiang, Xiao-Ling; Feng, Qiao; Li, Wei-Hong; Xu, Min; Kang, Jun-Sheng; Wei, Li-Xin
Abstract: In the present work we undertook the complete mitochondrial genome sequencing of an important hepatic cirrhosis model inbred C57BL/6 strain for the first time. Its mitogenome was 16, 312 bp and coding 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes. A total of 96 SNPs were examined when compared to reference BN sequence.